Impact of large landslides, mitigation measures - Schneider, Jean F.; Gruber, Fabian E.; Mergili, Martin (Italian journal of engineering geology and environment, 2013)
<span data-sheets-value="{"1":2,"2":"Besides existing landslide dammed lakes there is evidence of former cases in the high-mountain areas of Europe, Asia and America. In the Holocene, large landslides have repeatedly dammed lakes. Numerous prehistoric, historic and recent cases are evident where the dams could not resist the pressure of the impounding water. The result were flood waves characterized by particularly high peak discharges and long travel distances, leading to disasters where interfering with populated lands downstream. Even though most dam failures occur in the early phase after formation, lakes may also drain suddenly at later stages. Case studies from Central Asia and Northern Pakistan are employed in order to exemplify the involved phenomena regarding dam formation, outburst mechanisms and flood wave propagation. A particular focus is put on discussing the options for disaster risk reduction and hazard mitigation."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">Besides existing landslide dammed lakes there is evidence of former cases in the high-mountain areas of Europe, Asia and America. In the Holocene, large landslides have repeatedly dammed lakes. Numerous prehistoric, historic and recent cases are evident where the dams could not resist the pressure of the impounding water. The result were flood waves characterized by particularly high peak discharges and long travel distances, leading to disasters where interfering with populated lands downstream. Even though most dam failures occur in the early phase after formation, lakes may also drain suddenly at later stages. Case studies from Central Asia and Northern Pakistan are employed in order to exemplify the involved phenomena regarding dam formation, outburst mechanisms and flood wave propagation. A particular focus is put on discussing the options for disaster risk reduction and hazard mitigation.